An Analysis of Concepts and Evidence on the Question of Whether IFRS Should be Conservative. (20th May 2015) - Barker, Richard; McGeachin, Anne
<x xml:space="preserve">Abstract</x> Do international accounting standards require conservative accounting? The IASB's conceptual framework suggests that they should not, while the research literature is largely silent on the matter, typically presuming conservatism to be an outcome of private contracting rather than standardized, public, general purpose financial reporting. In this paper, we analyze the actual requirements of IFRS. We find multiple examples of recognition requirements that lead to unconditional conservatism, measurement requirements that lead to conditional conservatism, and also presentation/disclosure requirements that further support a conservative reporting environment. These findings complement, support and deepen existing evidence in the empirical literature that accounting is in practice conservative. We show, however, that the requirements for conservatism in IFRS conflict with, first, the IASB's stated position in its conceptual framework that accounting should not be conservative and, second, the private contracting explanation for conservatism that is generally accepted in the literature. What is missing, and lies behind both conflicts, is an acknowledgement and understanding of the role of an agency/contracting perspective in enhancing the decision‐usefulness of general purpose accounting standards, given the information/incentive asymmetry and uncertainty that characterizes the real‐world context in which those standards operate. From a policy perspective, such an understanding would reconcile the IASB's conceptual framework with the actual requirements of IFRS. From a research literature perspective, such an understanding would re‐position accounting standards as central to the practice of accounting conservatism, which would in turn require revision to the generally accepted theory of a private contracting explanation for the empirical evidence of conservative accounting practice.